Synthesis process of monolayer transition metal dichalcogenides
By using a chemical vapor deposition method of metal sodium carbonate silicate as a growth promoter, the reliability and quality problems of the synthesis of single-layer transition metal ditelluride films are solved, and a single-layer TMD film suitable for new devices is achieved efficiently in APCVD.
Patent Information
- Application Number
- JP2024541758
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-01
- Filing Date
- 2023-02-01
- Publication Date
- 2025-01-30
AI Technical Summary
The prior art is difficult to achieve efficient and reliable large-scale synthesis of single-layer transition metal ditelluride (TMD) films, and traditional methods such as ALD and MOCVD have problems of poor quality or high cost.
Sodium silicate is used as a growth promoter and combined with chemical vapor deposition (CVD) technology, high-quality single-layer TMD films are prepared by controlling growth parameters in a single-zone furnace.
It realizes the maintenance of good photoelectric characteristics in APCVD and improves tolerance to growth parameter changes, and obtains a high-quality single-layer TMD film, which is suitable for new device applications.
Smart Images

Figure 2025502963000003 
Figure 2025502963000004 
Figure 2025502963000005
Abstract
Description
[Technical field]
[0001] The present disclosure relates to the field of semiconductor technology, and in particular to a process for preparing reliable synthesis of transition metal dichalocogenide (TMD) monolayers in atmospheric pressure chemical vapor deposition (APCVD) by using metal silicates as growth promoters that improve the growth resistance of the TMD monolayer films while maintaining good optoelectronic properties of the films. [Background technology]
[0002] The Background Discussion contains information that may be helpful in understanding the present invention. No admission is made that any of the information provided herein is prior art or relevant to the presently claimed invention, or that any publication specifically or implicitly referenced is prior art.
[0003] TMD monolayers offer a wealth of physical properties in their monolayer regime and have the potential to revolutionize the semiconductor industry by providing a new degree of control. However, a major hurdle to achieving this goal is the reliable large-scale synthesis of monolayers of these materials.
[0004] Standard techniques for monolayer TMD synthesis include atomic layer deposition (ALD), metal organic chemical vapor deposition (MOCVD) and APCVD. Techniques such as ALD usually yield polycrystalline films, but the quality of the films is poor. On the other hand, techniques such as MOCVD are too complicated and expensive to implement. On the other hand, APCVD is very sensitive to subtle changes in parameters. To overcome this limitation of APCVD systems, growth promoters are commonly used. However, most growth promoters have limited effectiveness or are difficult to obtain. CVD is considered the best candidate to achieve this goal, but reproducible large-scale synthesis of these materials is a great challenge, since this technique is very sensitive to minute changes in growth conditions.
[0005] Thus, there is a need in the art to provide new, improved, and highly efficient processes for the synthesis of single-layer TMDs. The present disclosure fulfills existing and other needs and generally overcomes deficiencies found in the prior art. Objective of the invention
[0006] An object of the present disclosure is to provide an efficient process for synthesizing monolayer TMDs on a substrate.
[0007] An objective of the present disclosure is to provide a reliable synthesis process for monolayer TMDs that improves the tolerance of the growth of TMD monolayer films to changes in growth parameters in APCVD while maintaining good optoelectronic properties.
[0008] Another objective of the present disclosure is to provide a reliable synthesis process for monolayer TMDs using sodium silicate, also known as water glass (WG), as a growth promoter.
[0009] Another object of the present disclosure is to provide techniques to achieve conformal growth of monolayer transition metal dichalcogenide films on textured substrates for novel device applications.
[0010] It is yet another object of the present disclosure to provide a monolayer transition metal dichalcogenide film having good optoelectronic properties. Summary of the Invention
[0011] These and other objects are achieved by the present disclosure, which in one aspect provides a process for the synthesis of monolayer TMDs that uses metal silicates as growth promoters to improve the resistance of these materials to changes in growth parameters.
[0012] In one aspect, the present disclosure provides a reliable synthesis process for transition metal dichalcogenide (TMD) monolayers using a single-zone furnace, the process comprising: (a) spin-coating a dilute aqueous solution of growth promoter, where sodium silicate is the growth promoter for the transition metal dichalcogenide (TMD) monolayer, onto a target substrate at 4000 rpm; (b) loading the sodium silicate coated substrate into a chemical vapor deposition (CVD) chamber along with a transition metal precursor and a chalcogen, such as elemental sulfur or selenium; (c) providing an inert gas selected from N2, Ar, H2, or combinations thereof as a carrier gas for synthesis of the transition metal dichalcogenide; (d) heating the CVD chamber to a desired reaction temperature and holding the reaction temperature to synthesize transition metal dichalcogenides (TMDs), which are deposited as a TMD monolayer on the sodium silicate coated substrate; (e) cooling the CVD chamber to room temperature to obtain a sodium silicate coated substrate comprising a TMD monolayer.
[0013] In one embodiment of the present disclosure, the growth promoter is sodium silicate used at a concentration ranging from at least 0.05% to 50%, such as at least 0.01%, at least 0.2%, at least 0.5%, at least 1%, at least 5%, at least 10%, at least 20%, or at least 50%. 0.5% is preferred.
[0014] In one embodiment of the present disclosure, the substrate is a substrate selected from the group consisting of doped or undoped quartz, silicon, or the active layer of a silicon-on-insulator (SOI) substrate. The substrate may be smooth or textured.
[0015] In one aspect of the present disclosure, the transition metal precursor is selected from the group consisting of tungsten (W) and molybdenum (Mo).
[0016] In one aspect of the present disclosure, the chalcogen is selected from the group consisting of sulfur, selenium, or a combination thereof.
[0017] In one embodiment of the present disclosure, the TMD monolayer comprises MoS2, MoSe2, WS2, WSe2, or a combination thereof.
[0018] In one embodiment of the present disclosure, the carrier gas for the synthesis of MoS2 and WS2 is argon, nitrogen or a mixture thereof. The carrier gas for the synthesis of MoSe2 and WSe2 is argon and a 10% hydrogen mixture.
[0019] In one embodiment of the present disclosure, the chalcogen can be heated separately and controlled to a range of 150° C. to 300° C. for supply of chalcogen during the reaction.
[0020] In one embodiment of the present disclosure, heating of the chalcogen is set to 200° C. for sulfur and 300° C. for selenium, with heating starting 5 minutes before the target temperature is reached and stopping after the reaction.
[0021] In one embodiment of the present disclosure, deposition of a TMD monolayer on the surface of a substrate is performed at a desired reaction temperature between 500 °C and 900 °C, with the temperature ramped at a rate of 5 °C / min until the reaction temperature is reached and maintained for 10 min to obtain interspersed triangles and 20 min to obtain a continuous film.
[0022] In one embodiment of the present disclosure, the process further comprises flushing the single-zone furnace tube with 500 sccm of argon gas for 5 minutes and maintaining a constant flow rate of 30 sccm for MoS2 or WS2 deposition and 200 sccm for WSe2 monolayer deposition throughout the reaction.
[0023] In another embodiment of the present disclosure, the sodium silicate coated substrate is placed with the sodium silicate coated smooth / textured side facing down in a quartz tube of a single zone furnace for depositing a monolayer of WS2 or WSe2 synthesized at 850 °C.
[0024] In accordance with this disclosure or another embodiment, the sodium silicate coated substrate is placed in a quartz tube of a single zone furnace with the sodium silicate coated smooth / textured side facing down for depositing a monolayer of MoS2 synthesized at 500°C and with the silicate coated smooth side facing up for depositing a monolayer of MoS2 synthesized at 600°C.
[0025] In accordance with this disclosure or another embodiment, the sodium silicate coated substrate is placed with the sodium silicate coated smooth / textured side facing up in a separate boat away from the MoO precursor in a quartz tube in a single zone furnace to deposit a monolayer of MoS2 / MoSe2 synthesized at 700°C or higher.
[0026] In one embodiment of the present disclosure, the CVD can be atmospheric pressure chemical vapor deposition.
[0027] Various objects, features, aspects and advantages of the present subject matter will become more apparent from the following detailed description of preferred embodiments. [Brief description of the drawings]
[0028] [Figure 1] Schematic of the fabrication process of a TMD monolayer in a typical CVD setup. [Diagram 2]Comparison of MoS2 growth using NaCl and sodium silicate. (a) Schematic of growth showing good growth on sodium silicate coated substrate (shown as WG coated) and almost no growth on NaCl coated substrate. (b) Optical microscope image of substrate coated with sodium silicate as growth promoter after growth. (c) Optical microscope image of substrate coated with NaCl as growth promoter after growth. Scale bar is 50 μm. It is clear that sodium silicate is clearly superior to NaCl under the same conditions. (d) TGA of NaCl+MoO3 mixture and sodium silicate+MoO3 mixture. TGA of NaCl+MoO3 mixture starts only after 380 °C, while sodium silicate+MoO3 mixture starts to evaporate slowly even at a low temperature of 100 °C, suggesting high reactivity of the mixture. Slow weight loss of sodium silicate+MoO3 indicates a stable reaction. [Diagram 3] Measurements of the electrical properties of monolayer MoS2 are shown. (a) Dark current and photocurrent from the MoS2 device. The device produces a good photocurrent of over 5 A. The light source is a 405 nm LED with 12 mW / cm2 intensity. (b) Transient photoresponse of the device in the presence of 405 nm LED illumination. (c) Source-drain voltage sweep of the device at different gate voltages. (d) Source-drain current vs. back-gate voltage sweep of the MoS2 device used to measure the mobility of the device. (e) and (f) Mobility statistics of devices fabricated on monolayer MoS2 synthesized with NaCl and WG, respectively. [Figure 4] Photograph of continuous, large-area, single-layer TMDs grown on a 1-inch quartz substrate, taken alongside an uncoated quartz substrate for comparison. [Diagram 5]Measurement of the electrical properties of a continuous film. (a) Photograph of the measurement system measuring the electrical properties of a one centimeter long MoS2 monolayer film. (b) The optical microscope image shows a clean monolayer with a few areas of uncoated substrate. The scale bar is 50 μm. (c) Schematic of the entire measurement system, with the inset showing a photograph of the continuous MoS2 film during measurement. [Figure 6] Optical microscope images of MoS2 grown on substrates coated with sodium silicate at various concentrations (0.05%-50%). All concentrations yielded a monolayer, but the 0.5% concentration gave good coverage and did not change the color of the substrate, indicating a very thin and uniform coating. Higher concentrations resulted in a thicker coating layer, which does affect the substrate color. At lower concentrations, growth proceeds towards the edges, indicating that the coating thickness at 4000 rpm is not optimal. [Figure 7] (a) shows an optical image of a monolayer TMD grown on a 300 nm SiO2 trenched on a Si substrate. (b) and (c) are FESEM images of the monolayer TMD grown in the very narrow trench in (a). [Figure 8] (a) and (b) are SEM images of a TMD monolayer conformally grown on a patterned surface with sharp features with a radius of curvature of 20 nm, (b) shows a magnified version of the structure with a TMD monolayer conformally grown on it, and (c) and (d) are FESEM images of a TMD monolayer grown on patterned silicon with small hemispheres that form a hexagonal lattice. [Figure 9] The optical properties of the substrate are shown in Figure 8(a). (a) shows a single shot PL image showing a clear increase in PL intensity along the line, (b) shows a line scan of the intensity along the arrow marked in figure (a). (c) shows the fitted PL spectrum in the region of maximum PL intensity, showing a clear increase in the trionic peak intensity. [Figure 10] (a) and (b) show schematic diagrams of the PL emission from the substrate and the corresponding mechanism during operation. [Figure 11] Optical microscope images of different TMDs grown on SiO2 on a Si substrate are shown. [Figure 12] The PL of different monolayer TMDs is shown. Characteristic PL peaks distinguish individual TMDs and the high PL is consistent with the monolayer nature of the TMDs, as monolayers have very high PL intensity. [Figure 13] (a) and (b) show PL images of WS2 monolayers taken by fluorescence microscopy. The PL spectrum in (c) shows that the PL from WS2 monolayers is more than 1000 times stronger than that from bilayers. [Figure 14] 1 shows Raman spectra from different monolayer TMDs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0029] The following is a detailed description of the embodiments of the present disclosure. The embodiments are detailed enough to clearly communicate the present disclosure. However, the amount of detail provided is not intended to limit the anticipated variations of the embodiments. On the contrary, it is intended to cover all modifications, equivalents, and alternatives that are within the spirit and scope of the present disclosure as defined by the appended claims.
[0030] Throughout the following specification, unless the context requires otherwise, the word "comprise" and variations thereof, such as "comprises" and "comprising" are intended to be interpreted in their open and inclusive sense of "including, but not limited to."
[0031] References throughout this specification to "one embodiment" or "one embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment. Thus, the appearances of the phrases "in one embodiment" or "in one embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment. Furthermore, the particular features, structures, or characteristics may be combined in any suitable manner in one or more embodiments.
[0032] As used in this specification and the appended claims, the singular forms "a," "an," and "the" include the plural reference unless the context clearly dictates otherwise. It should also be noted that the term "or" is typically used in its sense to include "and / or" unless the context clearly dictates otherwise.
[0033] In some embodiments, the numerical values expressing properties such as amounts of ingredients, concentrations, reaction conditions, and the like, used to describe and claim certain embodiments of the invention should be understood as being modified in some cases by the term "about". Accordingly, in some embodiments, the numerical parameters set forth in the written description are approximations that may vary depending on the desired properties sought to be obtained by a particular embodiment. In some embodiments, the numerical parameters should be construed in light of the number of reported significant digits and by applying ordinary rounding techniques. Notwithstanding that the numerical ranges and parameters setting forth the broad scope of some embodiments of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as practicable.
[0034] Recitation of ranges of values herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, and unless otherwise indicated herein, each separate value is incorporated herein as if it were individually set forth herein.
[0035] All processes described herein can be performed in any suitable order unless otherwise indicated herein or clearly contradicted by context. Any and all examples provided with respect to specific embodiments herein, or the use of exemplary language (e.g., "such as"), are intended merely to better illustrate the invention and do not limit the scope of the invention as otherwise claimed. No language in the specification should be construed as indicating any non-claimed element essential to the practice of the invention.
[0036] The headings and abstracts of the invention provided herein are for convenience only and do not interpret the scope or meaning of the embodiments.
[0037] The following description provides a number of exemplary embodiments of the inventive subject matter. Although each embodiment represents a single combination of inventive elements, the inventive subject matter is considered to include all possible combinations of the disclosed elements. Thus, if one embodiment includes elements A, B, and C, and a second embodiment includes elements B and D, the inventive subject matter is considered to include any other remaining combinations of A, B, C, or D, even if not explicitly disclosed.
[0038] It should also be understood that the present invention can be embodied in various ways, such as a system, a method, or a device. These implementations, or other forms that the present invention may take, may be referred to herein as processes. In general, the order of steps of disclosed processes may be varied within the scope of the present invention.
[0039] The present disclosure generally relates to a process for preparing reliable synthesis of transition metal dichalcogenide (TMD) monolayers by using metal silicates as growth promoters.
[0040] In one embodiment, the present invention relates to a disclosure providing a process for reliable synthesis of transition metal dichalcogenide (TMD) monolayers using a single-zone furnace, the process comprising: (a) spin-coating a dilute aqueous solution of growth promoter, where sodium silicate is the growth promoter for the transition metal dichalcogenide (TMD) monolayer, onto a target substrate at 4000 rpm; (b) loading the sodium silicate coated substrate into a chemical vapor deposition (CVD) chamber along with a transition metal precursor and a chalcogen, such as elemental sulfur or selenium; (c) providing an inert gas selected from N2, Ar, H2, or combinations thereof as a carrier gas for synthesis of the transition metal dichalcogenide; (d) heating the CVD chamber to a desired reaction temperature and holding the reaction temperature to synthesize transition metal dichalcogenides (TMDs), which are deposited as a TMD monolayer on the sodium silicate coated substrate; (e) cooling the CVD chamber to room temperature to obtain a sodium silicate coated substrate comprising a TMD monolayer.
[0041] In one embodiment of the present disclosure, the growth promoter is sodium silicate used at a concentration ranging from at least 0.05% to 50.0%. For example, at least 0.1%, at least 0.2%, at least 0.3%, at least 0.4%, at least 0.5%, at least 0.6%, at least 0.7%, at least 0.8%, at least 0.9%, or at least 1.0%. When the rpm is 4000, 0.5% is preferred. The concentration may vary for different rpm.
[0042] In one embodiment of the present disclosure, the precursors can be delivered in the gas phase during the reaction.
[0043] In one embodiment of the present disclosure, the chalcogen is selected from sulfur or selenium or a combination thereof.
[0044] In one embodiment of the present disclosure, the substrate of interest is a semiconductor substrate selected from the group consisting of doped or undoped silicon, or an active layer of a silicon-on-insulator (SOI) substrate, or a quartz substrate. The substrate of interest may include a group IV semiconductor material layer (e.g., Si, Ge, SiGe, GeSn, etc.), a group III-V semiconductor material layer, or a group II-VI semiconductor material layer, etc. The substrate can also be any material, such as sapphire, mica, quartz, etc., as long as it can withstand the temperature.
[0045] In one embodiment of the present disclosure, the TMD monolayer comprises MoS2, WS2, WSe2, MoSe2, MoTe2, WTe2, or a combination thereof.
[0046] In another embodiment of the present disclosure, the thickness of the TMD monolayer ranges from 0.7 nm to 1 μm.
[0047] In one embodiment of the present disclosure, the deposition of the transition metal dichalcogenide on the surface of the substrate is carried out at a temperature ranging from 500° C. to 900° C. In another embodiment of the present disclosure, the temperature range depends on the precursors used and the TMDs being synthesized.
[0048] In one embodiment of the present disclosure, the precursors and substrate are present in amounts between 10 mg and 500 mg (depending on the TMDs being grown, the temperature of the synthesis, and the precursors used).
[0049] In one embodiment of the present disclosure, the chalcogen can be heated separately and controlled in the range of 150° C. to 300° C. for supply of chalcogen during the reaction.
[0050] In one embodiment of the present disclosure, the heating of the chalcogen is set to 200° C. for sulfur and 300° C. for selenium, with heating starting 5 minutes before the target temperature is reached and stopping after the reaction.
[0051] In one embodiment of the present disclosure, deposition of a transition metal dichalcogenide monolayer on the surface of a substrate is carried out at a desired reaction temperature between 500°C and 900°C, where the temperature is increased at a rate of 5°C / min until the reaction temperature is reached and maintained for 10 minutes to obtain sparse triangles and 20 minutes to obtain a continuous film.
[0052] In one embodiment of the present disclosure, the process further comprises flushing the single-zone furnace tube with 500 sccm of argon gas for 5 minutes and maintaining a constant flow rate of 30 sccm for MoS2 or WS2 deposition and 200 sccm for WSe2 monolayer deposition throughout the reaction.
[0053] In one embodiment of the present disclosure, the sodium silicate coated substrate is placed with the sodium silicate coated smooth / textured side facing down in a quartz tube of a single zone furnace for depositing a monolayer of WS2 or WSe2 synthesized at 850 °C.
[0054] In one embodiment of the present disclosure, the sodium silicate coated substrate is placed in a quartz tube of a single zone furnace with the sodium silicate coated smooth / textured side facing down for depositing a monolayer of MoS2 synthesized at 500°C and the silicate coated smooth side facing up for depositing a monolayer of MoS2 synthesized at 600°C. Working Example
[0055] The present disclosure will be further described in the form of the following examples. However, it should be understood that the above examples are merely illustrative and do not limit the scope of the present invention. Various changes and modifications to the disclosed embodiments will be apparent to those skilled in the art. Such changes and modifications can be made without departing from the scope of the present invention.
[0056] Example 1: Fabrication of a TMD monolayer in a typical CVD configuration CVD growth was performed in a 3.5 cm diameter quartz tube in a single-zone furnace. There is a separate heater just outside the furnace attached to the tube to heat the chalcogens separately. Argon / nitrogen gas was used as the carrier gas for the synthesis of MoS2 and WS2. An argon-hydrogen mixture (10% H2) was used to synthesize WSe2. The alumina boat containing the chalcogens is placed just outside the furnace with a separate heater attached, as shown in Figure 1. The boat containing the transition metal precursor is placed 15 cm downstream from the boat containing the chalcogens, as shown in Figure 1(a). To synthesize WS2 and WSe2 as well as MoS2 at temperatures below 700 °C, Figure 1 configuration "a" was used. For WS2, WSe2 (both synthesized at 850 °C) and MoS2 (synthesized at 500 °C), the substrates were held with the SiO2-coated smooth side facing down, and for MoS2 synthesized at 600 °C, the SiO2-coated side was facing up. The change in position was to compensate for the lower evaporation of the precursors at lower temperatures. In most of the studies on MoS2 growth at 700 °C, configuration "b" from Figure 1 was used. Here, the substrate was kept facing up on a separate boat 2 cm away from the boat containing the transition metal precursors. First, the tube was flushed with 500 sccm of argon gas for 5 min, then the flow rate was reduced and kept at a constant value throughout the reaction. The flow rates for MoS2 and WS2 were 30 sccm, and for WSe2 200 sccm. The furnace was ramped at a rate of 5 °C / min until the reaction temperature was reached and maintained for no more than 10 min to obtain scattered triangles and 20 min to obtain a continuous film. The heaters for the chalcogens were set at 200 °C for sulfur and 300 °C for selenium. The heaters were turned on 5 min before reaching the target temperature and turned off after the reaction. The entire setup was allowed to cool naturally and the samples were removed after cooling to room temperature.
[0057] Example 2: Comparison of the effectiveness of sodium silicate and NaCl for the growth of MoS2 monolayers under the same conditions To confirm the effect of using sodium silicate as a growth promoter, its growth was compared to that with NaCl, a very common growth promoter. A 0.5% sodium silicate solution and a 0.001 molar NaCl solution were spin-coated onto the substrate. The amount of MoO3 was reduced to 10 mg to reduce the precursor concentration in the reaction, and the reaction time was set to 10 min at 700 °C. To ensure that the growth conditions were similar, the substrates coated with sodium silicate and salt alternately were placed in separate boats, as shown in Figure 2a. After the reaction was run for 10 min, good growth was observed on the sodium silicate-coated substrate, and little or no growth was observed on the NaCl-coated substrate. This indicated that sodium silicate is a much more efficient growth promoter than NaCl. Thermogravimetric analysis (TGA) of NaCl mixed with MoO3 was performed and compared to dry WG powder mixed with MoO3. As can be seen from Figure 2d, the WG mixture shows a steady decrease in its mass even at temperatures as low as 100 °C, while no weight loss was observed up to 380 °C for the NaCl mixture. From the TGA, it is evident that the reaction of WG with MoO3 occurs more readily than NaCl even at lower temperatures.
[0058] Example 3: Comparison of electrical properties of MoS2 monolayers grown using sodium silicate and NaCl Figure 3 shows the photoelectrical characteristics of MoS2 synthesized using sodium silicate. The devices were fabricated using photolithography followed by thermal vapor deposition of 5 nm Cr followed by 65 nm Au to fabricate the active device on a monolayer film on 300 nm SiO2 on a Si substrate. SiO2 was used as a dielectric for field effect studies such as FETs. The photoresponse was studied using a 405 nm LED with an intensity of 10 mW / cm2 controlled using an Arduino. The dark I-V characteristics of the device shown in Figure 3a were linear, confirming the formation of an ohmic contact. The device also shows a good photoresponse with an order of magnitude change in current when illuminated with a 405 nm light emitting diode (LED). The time resolved photoresponse of the device in Figure 3b was studied at a bias of 1 V by illuminating the device with a 405 nm LED at 1 min intervals. The Isd-Vsd characteristics showed a linear relationship (Figure 3c) over a wide voltage range, also suggesting an ohmic contact at room temperature. Typical source drain current vs gate voltage for both devices is given in Figure 3c. Figure 3d shows the Isd-Vg plots for devices fabricated using MoS2 synthesized using NaCl and sodium silicate for comparison. For comparison, mobility statistics for devices using sodium silicate and salt are also shown in Figures 3e and 3f. Devices fabricated using MoS2 grown using sodium silicate showed mobilities in the range of 15-35 cm2 V-1s-1 with Ion / Ioff ratios of 105-106. For comparison, devices were also fabricated on MoS2 synthesized with NaCl (salt). Typical mobility values for devices using samples synthesized using salt were in the range of 0.1-1 cm2 V-1s-1. This is much lower (more than an order of magnitude) than those exhibited by samples synthesized using sodium silicate. The performance of samples synthesized using sodium silicate was clearly superior to that of those grown using NaCl. The mobility of the devices was calculated from the linear region of the transfer curve using the following equation: JPEG2025502963000001.jpg11170In the formula, L is the channel length, W is the channel width, C g is the relation where ε0=8.854×10-12 Fm-1, εr is 3.9 for SiO2, and d is the thickness of the SiO2, which is 300 nm here.
[0059] Example 4: Growth of centimeter-scale MoS2 monolayer films and their electrical conductivity Figure 4 shows a continuous monolayer MoS2 film grown on a 1-inch quartz plate placed next to a quartz plate without a MoS2 monolayer to demonstrate the scalability of the growth. Figure 5 shows measurements performed on the continuous monolayer MoS2 film. The devices showed that centimeter-sized films are electrically continuous and produce adequate photocurrents.
[0060] Example 5: Monolayer TMD grown at various concentrations and conformal growth of TMD monolayers Figure 6 shows images of monolayer MoS2 grown on SiO2 / Si substrates using different concentrations of sodium silicate from 0.05% to 50%. Good growth was observed on all substrates, but yields were low on substrates using concentrations below 0.5%, and when concentrations exceeded 5%, the color of the substrate was affected by a thick coating of sodium silicate. Figure 7a shows an optical image of a TMD monolayer conformally grown on a patterned substrate, and Figure 7(b) and (c)) show FESEM images of the coating on a trenched SiO2 on a Si substrate. Figure 8 shows SEM images of a TMD monolayer conformally grown on a patterned surface. (a) shows the coating on a sharp surface with a radius of curvature of 20 nm, (b) shows a magnified image of the textured substrate, and (c) and (d) show the conformal coating on a textured substrate that covered the entire substrate with a lattice of small hemispherical shapes.
[0061] Example 6: Funneling effect from conformally grown MoS2 monolayers Figure 9a shows a single-shot PL image from one of the textured substrates. It clearly shows the enhancement of PL intensity in the region of curvature caused by the funnel effect. Figure 9b is a graph showing the PL intensity as a function of pixel position along the arrow in Figure 9a. Figure 9c shows the PL spectrum from the region of maximum PL intensity. The PL spectrum from this region clearly shows the enhancement of the trion peak in the PL spectrum of MoS2, indicating the possibility of engineering the optical properties of TMDs by conformal coating for new applications such as photonic crystals. Figure 10a and b show the schematic of the light emission from the textured substrate and the mechanism of light emission, respectively.
[0062] Example 7. Characterization of TMD monolayers synthesized using sodium silicate as a growth promoter Figure 11 shows optical images of MoS2, WS2, and WSe2 TMD monolayers synthesized using sodium silicate as a growth promoter for shorter growth times on 300 nm SiO2 on Si substrates. Figure 12 shows photoluminescence spectra of synthesized MoS2, MoSe2, WS2, and WSe2 TMD monolayers. Figure 13 compares the PL of monolayer and bilayer WS2 synthesized using sodium silicate as a growth promoter. Figure 14 shows Raman spectra of MoS2, WS2, and WSe2 TMDS synthesized using sodium silicate as a growth promoter. Advantages of the present disclosure
[0063] The present disclosure provides a process for the synthesis of transition metal dichalcogenide (TMD) monolayers using sodium silicate, an inexpensive, easy to handle, and commonly available material, as an excellent growth promoter for growing TMD monolayers of high optoelectrical quality using atmospheric pressure chemical vapor deposition.
[0064] The present disclosure provides a process for the synthesis of transition metal dichalcogenide (TMD) monolayers using sodium silicate that is highly effective in facilitating growth by improving tolerance to subtle changes in growth parameters that can adversely affect synthesis, much more so than commonly used growth promoters such as NaCl.
[0065] One of ordinary skill in the art will understand that the amounts and types of each component may be used in different combinations or alone, and all such variations and combinations are intended to be within the scope of the present disclosure.
[0066] The above examples are merely illustrative and do not limit the scope of the present invention. Various changes and modifications to the disclosed embodiments will be apparent to those skilled in the art. Such changes and modifications can be made without departing from the scope of the present invention.
Claims
1. A process for conformal growth of transition metal dichalcogenide (TMD) monolayers on textured or smooth surfaces using sodium silicate as a growth promoter, (a) spin-coating onto a substrate a dilute aqueous solution of a growth promoter, where sodium silicate acts as a growth promoter for a transition metal dichalcogenide (TMD) monolayer; (b) loading the sodium silicate coated substrate into a chemical vapor deposition (CVD) chamber along with a transition metal precursor and a chalcogen, such as elemental sulfur or selenium; (c) N 2 , Ar, H 2 or a combination thereof as a carrier gas for TMD synthesis; (d) heating the CVD chamber to a desired reaction temperature and holding at the reaction temperature to synthesize TMDs that are deposited as a TMD monolayer on the sodium silicate coated substrate; (e) cooling the CVD chamber to room temperature to obtain a sodium silicate coated substrate comprising a TMD monolayer.
2. 2. The process according to claim 1, characterized in that the concentration of the growth promoter can be from 0.05% to 50%, the optimum coating used being 0.5% sodium silicate.
3. 2. The process according to claim 1, characterized in that the spin coating is carried out at 1000 to 10,000 rpm, the optimum speed used being 4000 rpm.
4. 10. The process of claim 1, wherein the transition metal precursor is selected from the group consisting of transition metal oxides, chlorides, elemental metals, or other vaporizable forms of transition metals.
5. 2. The process of claim 1, wherein the transition metal precursor is selected from the group consisting of tungsten (W) and molybdenum (Mo).
6. The TMD monolayer is MoS 2 , MoSe 2 , W.S. 2 , WSe 2 or a combination thereof.
7. The MoS 2 and W.S. 2 2. The process according to claim 1, wherein the carrier gas for the synthesis is argon or nitrogen.
8. The MoSe 2 and WSe 2 2. The process of claim 1, wherein the carrier gas for the synthesis is a mixture of argon and 10% hydrogen.
9. 2. The process of claim 1, wherein the CVD is atmospheric pressure chemical vapor deposition (APCVD).
10. 2. The process of claim 1, wherein the substrate of interest is a semiconductor substrate selected from the group consisting of doped or undoped silicon, or the active layer of a silicon-on-insulator (SOI) substrate, or an insulator such as sapphire, quartz, F-mica, etc.
11. 2. The process of claim 1, wherein the chalcogen is heated separately in the temperature range of 150° C. to 300° C. by placing the chalcogen just outside a furnace for supplying the chalcogen during the reaction.
12. 2. The process of claim 1, wherein the chalcogen is selected from the group consisting of sulfur, selenium, or a combination thereof.
13. The process according to claims 8 to 9, characterized in that the heating of the chalcogen is set to 200°C for sulfur and 300°C for selenium, heating is started 5 minutes before the target temperature is reached, and heating is stopped after the reaction.
14. 2. The process according to claim 1, characterized in that the deposition of the transition metal dichalcogenide monolayer on the surface of the substrate is carried out at a desired reaction temperature between 500° C. and 900° C., the temperature is increased at a rate of 5° C. / min until the reaction temperature is reached and maintained for 10 minutes to obtain sparse triangles and 20 minutes to obtain a continuous film.
15. Additionally, the single-zone furnace tube was flushed with 500 standard cubic centimeters per minute (sccm) of argon gas for 5 minutes to maintain the MoS throughout the reaction. 2 Or W.S. 2 30 sccm for deposition, WSe 2 Or MoSe 2 The process of any one of claims 1 to 13, comprising maintaining a constant flow rate of 200 sccm for monolayer deposition.
16. The sodium silicate coated substrate was prepared using WS synthesized at 850° C. 2 Or WSe 2 The process according to any one of claims 1 to 14, characterized in that the sodium silicate-coated smooth side is placed facing downwards in a quartz tube of a single-zone furnace for depositing a monolayer of
17. The sodium silicate-coated substrate was prepared using MoS synthesized at 500° C. 2 MoS was synthesized at 600 °C in a quartz tube in a single-zone furnace with the sodium silicate-coated side facing downwards to deposit a monolayer of 2 The process according to any one of claims 1 to 14, characterized in that the silicate-coated smooth side is facing up for depositing a monolayer of
18. The sodium silicate-coated substrate is made of MoS synthesized at 700° C. or higher. 2 and MoSe 2 The process according to any one of claims 1 to 14, characterized in that the sodium silicate-coated side is placed facing up on another boat downstream to deposit a monolayer of